2011
DOI: 10.1631/jzus.b1000373
|View full text |Cite
|
Sign up to set email alerts
|

Artesunate inhibits growth and induces apoptosis in human osteosarcoma HOS cell line in vitro and in vivo

Abstract: This paper aims to investigate the effects of artesunate (ART) on growth and apoptosis in human osteosarcoma HOS cell line in vitro and in vivo and to explore the possible underlying mechanisms. Cell viability was measured by 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide (MTT) assay. The induction of apoptosis was detected by light and transmission electron microscopy and flow cytometry. Western blot analysis was used to investigate the related mechanisms. Nude mice were further employed to inve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
28
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(30 citation statements)
references
References 34 publications
2
28
0
Order By: Relevance
“…Recently, Xu et al demonstrated that the antitumor mechanism of artesunate was achieved by inhibiting cell cycle progression and inducing apoptosis in human osteosarcoma cells in vitro and in vivo [26]. In this study, FCM was used to detect changes in cell cycle progression, and it was found that as the artesunate concentration increased, the proportion of MG-63 cells in the G2/M and S phases gradually increased while the proportion of cells at G0/G1 phase gradually decreased, which indicated that artesunate inhibited the progression of cell cycle thereby restraining cell proliferation.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Xu et al demonstrated that the antitumor mechanism of artesunate was achieved by inhibiting cell cycle progression and inducing apoptosis in human osteosarcoma cells in vitro and in vivo [26]. In this study, FCM was used to detect changes in cell cycle progression, and it was found that as the artesunate concentration increased, the proportion of MG-63 cells in the G2/M and S phases gradually increased while the proportion of cells at G0/G1 phase gradually decreased, which indicated that artesunate inhibited the progression of cell cycle thereby restraining cell proliferation.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, the effect on total metabolic activity was not reversed up to 96 hpt. The explanation for this apparent discrepancy is probably linked to a cell cycle arrest in G 0 or G 2 , as previously demonstrated in other cells (39,(54)(55)(56). When the effect of artesunate waned, a high proportion of the synchronized cells moved into the S phase and incorporated BrdU in their DNA, whereas the metabolic activity was still reduced due to reduced cell numbers.…”
Section: Discussionmentioning
confidence: 72%
“…Interestingly, while some found simultaneously increased numbers of cells in G 0 /G 1 phase (43) (45), others described increased numbers of cells in G 2 /M phase (46). Apparently, artesunate also induced apoptosis in many cancer cell lines (43,45,46). Since we did not detect any sub-G 1 -phase fraction when performing flow cytometry, we concluded that artesunate at 10 and 40 M does not induce apoptosis in RPTECs.…”
Section: Discussionmentioning
confidence: 72%
“…This is also supported by our real-time proliferation analysis, where only cells treated with artesunate at concentrations of 10 M or less, which were possibly arrested in G 0 phase, spontaneously reinitiated proliferation after 40 to 50 h. Of note, artesunate and dihydroartemisinin have previously been described to decrease the numbers of cells in S phase in A431 human epidermoid carcinoma cells (43), cells of the human leukemia cell line K562 (44), and cells of the murine myeloma cell line SP2/0 (45). Interestingly, while some found simultaneously increased numbers of cells in G 0 /G 1 phase (43) (45), others described increased numbers of cells in G 2 /M phase (46). Apparently, artesunate also induced apoptosis in many cancer cell lines (43,45,46).…”
Section: Discussionmentioning
confidence: 99%